The obligations and rights of the pastor of a parish according to the Code of Canon Law. - Sweeney, Edward A. (University of Ottawa (Canada), 1999)
The office of Pastor of a parish is an ecclesial institute constituted by the Church to be at the service of its threefold mission of teaching, sanctifying and ruling under the leadership of the diocesan bishop. As an institute created by positive law, this office has obligations and rights proper to it. Therefore, as a holder of this office, a pastor. of a parish is the subject of these obligations and rights. And these obligations and rights are to be properly understood and diligently exercised for the good of the Church and for the salvation of souls. Through its new theological insights, the Second Vatican Council ushered in significant changes in the understanding of the nature and scope of this office. The 1983 Code of Canon Law tried to translate those insights and changes into legal language in the revised legislation on the pastor of a parish. The Council described the parish in terms of a Eucharistic community, which, in communion with the Universal Church, in a special way makes Christ's Church present at a particular time and place through the shared faith of its members, clergy and laity together, its liturgical, catechetical charitable and social activities. It is at the level of a parish that the universal Church finds its concrete realization. And its pastor plays an important role in its life and activity. The object of this study, therefore, are the obligations and rights which the 1983 Code attributes to the office of pastor of a parish. There are several canons in the 1983 Code which express obligations and rights, explicitly in some instances and implicitly in others. The principal obligation of a pastor of a parish is to serve the faithful by leading the teaching, sanctifying and administrative activities of the faith community. Most of the rights attached to the office of a pastor are those which enable the pastor usefully and faithfully to fulfil the obligations entailed in his leadership role. Readily acknowledging that the pastor's obligations are so extensive that he will need various kinds of assistance, both the Second Vatican Council and the 1983 Code stipulate that other members of the parish community, clergy and laity together, are to cooperate with the pastor and to provide such help as the pastor needs. This principle implies that the ecclesial dimensions of the office of pastor of a parish cannot be totally circumscribed by a mere listing of the obligations and rights either explicitly or implicitly stated in the positive legislation. As an ecclesial institute, this office by its very nature demands that it be exercised in collaboration with all the members of a parish community.
Keywords: Law.